Amorphous-nanocrystalline gradient multilayer structure coating as well as preparation method and application thereof
By forming amorphous-nano-crystal gradient multi-layer structural coating on the surface of stainless steel, the problem of defects in existing zirconium nitride coatings is solved, significantly improving the hardness and wear resistance of stainless steel, achieving higher fatigue resistance and Extensibility.
Patent Information
- Application Number
- CN202411671865.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
AI Technical Summary
The existing zirconium nitride coatings have microcracks and pore defects during the growth process, resulting in insufficient strength, hardness, wear resistance and corrosion resistance of the coating. The single-layer coating is prone to cracking and peeling, which cannot effectively improve the surface of stainless steel. wear resistance.
Using amorphous-nanocrystal gradient multi-layer structure coating, the Zr layer, ZrNSi50 layer, ZrNSi40 layer, ZrNSi30 layer, ZrNSi20 layer and ZrN layer are deposited on the stainless steel surface in sequence to form a gradient structure with strong inner toughness and external strength, and the coating is enhanced. The bonding force of the substrate.
It significantly improves the hardness and wear resistance of stainless steel, and the wear rate is reduced to 0.62±0.05×10-4mm3/(N·m), which is 8 times smaller than the uncoated stainless steel substrate, enhancing the fatigue resistance and ductility of the coating. .
Smart Images

Figure CN119506808A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hard coatings, and in particular relates to an amorphous-nanocrystalline gradient multilayer structure coating and a preparation method and application thereof. Background Art
[0002] AISI304 austenitic stainless steel has comprehensive advantages such as high strength, good plasticity, good toughness and corrosion resistance, and is widely used in aerospace, petrochemical and medical equipment, machinery, construction and other fields. However, in order to improve the resistance to intergranular corrosion, the carbon content of AISI 304 is less than 0.03%, so the hardness is relatively low (200-250HV). Therefore, the hardness and wear resistance are greatly reduced. It is difficult to withstand severe wear in practical applications. At present, many surface modification technologies have been used to increase the service life of AISI304, such as nitriding, carburizing, shot peening, coating, electroplating, etc. Among them, surface coating is a widely used technology because it not only improves the hardness and wear resistance of the base material, but also improves the appearance and provides special functions without affecting the strength of the original base material.
[0003] Zirconium nitride (ZrN) is a The zirconium nitride coating is usually golden yellow and has a melting point of up to 3053K. In addition, it has high hardness, excellent wear resistance and thermal stability. Therefore, ZrN coatings are widely used in surface decoration, protection and corrosion resistance, cutting tools and wear resistance. However, zirconium nitride coatings usually grow along columnar crystals, and there are defects such as microcracks and pores at the grain boundaries, which affect the strength, hardness, wear resistance and corrosion resistance of the coating. In addition, there are great differences between the substrate and the coating in terms of chemical composition, crystal structure, expansion coefficient, and the presence of residual stress. Therefore, the single-layer coating is very easy to crack and peel off, and cannot improve the wear resistance of the stainless steel surface. Summary of the invention
[0004] In order to solve the problems in the prior art, the present invention provides an amorphous-nanocrystalline gradient multilayer structure coating and a preparation method and application thereof, so as to achieve the purpose of realizing a high-hardness wear-resistant coating by using an amorphous-nanocrystalline gradient multilayer structure. The present invention uses surface coating technology to improve the hardness of stainless steel while enhancing the bonding force between the coating and the stainless steel substrate, thereby increasing the wear resistance of stainless steel, improving the use strength of stainless steel, and expanding its application in the field of friction. The process is simple, the production efficiency is high, and it is conducive to promoting the large-scale application of stainless steel.
[0005] The present invention solves the technical problem by adopting the following technical solutions:
[0006] The present invention aims to provide an amorphous-nanocrystalline gradient multilayer structure coating, comprising a Zr layer, a ZrNSi50 layer, a ZrNSi40 layer, a ZrNSi30 layer, a ZrNSi20 layer and a ZrN layer deposited in sequence.
[0007] Nanocomposite superhard coating is formed by adding an appropriate amount of silicon element to the metal nitride coating to form a strong insoluble system, and a sharp and strong interface is formed through phase separation, so that the nanocomposite material has ultra-high strength. Studies have found that when the Si element content is about 8.0at.%, the coating hardness can reach the maximum value. However, with the further increase of Si content, the coating gradually changes from a nanocomposite structure to an amorphous structure, which leads to a decrease in hardness. On the other hand, the comprehensive performance of the coating can be improved by optimizing the structure, and it can be widely used in metal and ceramic coatings. Among them, the gradient structure can reduce the internal stress of the coating, improve the adhesion of the coating, inhibit crack propagation, and withstand greater shear stress. Studies have found that under the action of external force, the nanocrystals in the gradient nanocrystalline layer will coarsen or grow, so that the material can accommodate greater plastic strain, inhibit shear localization or instability in the gradient nanocrystalline layer, and help to obtain good ductility and high fatigue resistance. These refined microstructures have strong blocking ability and toughness, thereby improving the wear resistance of the coating.
[0008] Furthermore, in the coating, the Zr layer is 52-56 nanometers, the ZrNSi50 layer is 105-110 nanometers, the ZrNSi40 layer is 112-117 nanometers, the ZrNSi30 layer is 105-110 nanometers, the ZrNSi20 layer is 110-115 nanometers, and the ZrN layer is 92-97 nanometers.
[0009] A method for preparing an amorphous-nanocrystalline gradient multilayer structure coating adopts a multi-target magnetron sputtering coating system to deposit a Zr layer, a ZrNSi50 layer, a ZrNSi40 layer, a ZrNSi30 layer, a ZrNSi20 layer and a ZrN layer on the surface of a substrate from bottom to top in sequence through a magnetron sputtering deposition process.
[0010] (a) Zr, ZrN, ZrNSi20 and ZrNSi50 single-layer coatings deposited on silicon wafers using a multi-target magnetron sputtering system (M230, Vikaitech, China) for thickness and structure characterization. (b) Zr / ZrNSix double-layer coatings (i.e., Zr / ZrNSi) with different silicon contents deposited on AISI304 stainless steel and silicon wafers, with thickness, chemical state, crystal structure, hardness and wear resistance controlled by the silicon target power. (c) Thickness, chemical state, crystal structure, hardness and wear resistance of Zr / ZrNSi50 / ZrNSi40 / ZrNSi30 / ZrNSi20 / ZrN multilayer films (i.e., Zr / ZrNSi-Grad) deposited on AISI304 stainless steel and silicon wafers. The amorphous sublayer inside the coating has high plasticity, and the outer nanocrystalline sublayer has high hardness, forming a gradient structure that is tough inside and strong outside, which makes the gradient coating have excellent wear resistance.
[0011] Furthermore, in the magnetron sputtering deposition process, the argon gas introduced is 35-45 sccm, the nitrogen gas introduced is 10-20 sccm, and the deposition time is 170-190 min.
[0012] Furthermore, the magnetron sputtering target materials used are a zirconium target with a purity of 99.95% and a silicon target with a purity of 99.99%.
[0013] Furthermore, before the coating is deposited, the surface of the substrate is first polished to obtain a substrate with a mirror effect, and the substrate and the silicon wafer substrate are ultrasonically cleaned in anhydrous ethanol for 5-15 minutes to remove surface oil stains.
[0014] Furthermore, the treatment before coating deposition also includes a sputtering chamber vacuum exceeding 5×10 -6 After 30 to 400 sccm, argon gas with a flow rate of 30 to 50 sccm is introduced to generate argon ions under the action of a 50 W radio frequency power supply, and the substrate is ion-etched for 3 to 8 minutes to remove impurities adsorbed on the substrate surface.
[0015] An amorphous-nanocrystalline gradient multilayer structure coating or a method for preparing an amorphous-nanocrystalline gradient multilayer structure coating is used in preparing austenitic stainless steel surface coating.
[0016] Compared with the prior art, the beneficial technical effects of the present invention are:
[0017] 1. The present invention provides a Zr / ZrNSi50 / ZrNSi40 / ZrNSi30 / ZrNSi20 / ZrN amorphous-nanocrystalline gradient multilayer structure coating, wherein a Zr layer, a ZrNSi50 layer, a ZrNSi40 layer, a ZrNSi30 layer, a ZrNSi20 layer and a ZrN layer are sequentially deposited on a substrate, and the Si element is reduced from the Zr bonding layer upward to form an element gradient structure coating. At the same time, due to the reduction of the Si element, the Zr-N-Si coating is sequentially transformed from an amorphous structure to a nanocrystalline structure, so that the coating has the properties of being tough inside and strong outside. The hardness of the gradient multilayer structure coating can reach 19.3±0.7GPa, which can increase the hardness of the stainless steel substrate by 4.6 times, and its wear rate can be reduced to 0.62±0.05×10 -4 mm 3 / (N·m), which is 8 times smaller than that of the uncoated stainless steel substrate, greatly improving the wear resistance of stainless steel.
[0018] 2. The present invention provides a method for preparing a Zr / ZrNSi50 / ZrNSi40 / ZrNSi30 / ZrNSi20 / ZrN amorphous-nanocrystalline structure gradient multilayer film, which adopts physical vapor deposition, has a simple process, strong controllability, and the crystal growth control process only needs to control the physical structure of the Zr-N-Si layer by decreasing the power of the silicon target power supply from large to small. Due to the complete amorphization of the inner sublayer of the film layer, the expansion of the outer layer through cracks can be blocked, so that the toughness of the coating is increased, and the bonding force between the film layer and the substrate is greatly improved; in addition, due to the high degree of crystallization of the surface layer of the film layer, the hardness of the surface layer of the coating is significantly increased, which greatly improves the wear resistance of the film layer.
[0019] 3. The Zr / ZrNSi50 / ZrNSi40 / ZrNSi30 / ZrNSi20 / ZrN gradient multilayer structure coating provided by the present invention has uniform and dense film formation, strong bonding with the substrate, strong load resistance, and excellent wear resistance.
[0020] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented in accordance with the contents of the specification. In order to make the above contents of the present invention and its objectives, features and advantages more obvious and easy to understand, the specific implementation methods of the present invention are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a schematic diagram of the structures of Comparative Examples 1-3 and Example 1 of the present invention.
[0022] Figure 2 These are optical and FESEM cross-sectional views of Comparative Examples 1-3 and Example 1 of the present invention.
[0023] Figure 3 It is a diagram of element contents of Comparative Examples 1-3 in the present invention.
[0024] Figure 4 It is the GIXRD diagram of Comparative Examples 1-3 and Example 1 in the present invention.
[0025] Figure 5 It is the cross-sectional HRTEM image and selected area electron diffraction pattern of Example 1 of the present invention.
[0026] Figure 6 It is the loading and unloading curves and hardness curve diagram of AISI304, comparative examples 1-3 and embodiment 1 in the present invention.
[0027] Figure 7 It is the surface morphology and chemical composition diagram of the wear scar after friction between AISI304, Comparative Examples 1-3 and Example 1 in the present invention and AISI304 steel ball.
[0028] Figure 8 It is a comparison chart of the wear scar depth, width and wear rate of AISI304, comparative examples 1-3 and embodiment 1 in the present invention.
[0029] Fig. 9 This is a diagram of the wear scar surface and cross-sectional deformation of Example 1 of the present invention. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary illustrations and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0031] In addition, unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0032] Selection of coating system and substrate material: The coating machine used is the M230 multi-target magnetron sputtering coating system produced by Beijing Weikai Technology Co., Ltd. 304 stainless steel substrate (Φ = 20mm, thickness 3mm), silicon wafer substrate (20×20×0.5mm 3 ). Among them, the 304 stainless steel substrate is the main application scenario of the present invention, which is used to characterize the friction coefficient and wear rate of the film; the silicon wafer substrate is used to characterize the film thickness, surface / cross-sectional morphology, chemical composition, and hardness. The magnetron sputtering targets used to prepare the coating are Zr targets with a purity of 99.95% and Si targets with a purity of 99.99%.
[0033] Cleaning of substrate materials: Before coating deposition, the stainless steel substrate is first polished to obtain mirror-like stainless steel, and the stainless steel and silicon wafer substrates are ultrasonically cleaned in anhydrous ethanol for 5-15 minutes, preferably 10 minutes, to remove surface oil stains. In order to remove impurities adsorbed on the substrate surface, the vacuum degree in the sputtering chamber reaches 5×10 -6 When the pressure is above 50 Torr, argon gas is introduced at a flow rate of 30-50 sccm, preferably 40 sccm, to generate argon ions under the action of a 50 W radio frequency power supply, and the substrate is ion-etched for 3-8 minutes, preferably 5 minutes.
[0034] Example 1
[0035] Preparation of coating: A multi-target magnetron sputtering coating system (M230, Vikaitech, China) was used to deposit a 54nm zirconium layer, a 108nm ZrNSi50 layer, a 115nm ZrNSi40 layer, a 108nm ZrNSi30 layer, a 112nm ZrNSi20 layer, and a 94nm ZrN layer on the stainless steel surface from bottom to top through a magnetron sputtering deposition process, and an amorphous-nanocrystalline structure gradient multilayer film (ZrNSi-Grad) was obtained on the stainless steel surface. The specific deposition process parameters are shown in Table 1.
[0036] Example 2
[0037] Preparation of coating: A multi-target magnetron sputtering coating system (M230, Vikaitech, China) was used to deposit a 52nm zirconium layer, a 105nm ZrNSi50 layer, a 112nm ZrNSi40 layer, a 105nm ZrNSi30 layer, a 110nm ZrNSi20 layer, and a 92nm ZrN layer on the stainless steel surface from bottom to top through a magnetron sputtering deposition process, and an amorphous-nanocrystalline structure gradient multilayer film (ZrNSi-Grad) was obtained on the stainless steel surface. The specific deposition process parameters are shown in Table 1.
[0038] Example 3
[0039] Preparation of coating: A multi-target magnetron sputtering coating system (M230, Vikaitech, China) was used to deposit a 56nm zirconium layer, a 110nm ZrNSi50 layer, a 117nm ZrNSi40 layer, a 110nm ZrNSi30 layer, a 115nm ZrNSi20 layer, and a 97nm ZrN layer on the stainless steel surface from bottom to top through a magnetron sputtering deposition process, and an amorphous-nanocrystalline structure gradient multilayer film (ZrNSi-Grad) was obtained on the stainless steel surface. The specific deposition process parameters are shown in Table 1.
[0040] Comparative Example 1
[0041] Referring to Table 1, the difference between Comparative Example 1 and Example 1 is that Comparative Example 1 is a double-layer structure, the preparation parameters of the Zr bonding layer are the same as those of Example 1, the deposition time of the ZrN layer is 180 min, and the other parameters are the same as those of Example 1. After the sputtering is completed, the surface of the prepared stainless steel specimen changes from silvery white to golden yellow, and sample B-1 (ZrN) is prepared, and the coating thickness of sample B-1 is measured to be 625 nm.
[0042] Comparative Example 2
[0043] Referring to Table 1, the difference between Comparative Example 2 and Example 1 is that the silicon target power of the Zr-N-Si surface layer of Comparative Example 2 is a DC power supply of 20W, and the other parameters are the same as those of Example 1. After sputtering, the surface of the prepared stainless steel specimen changes from silvery white to black gray, and sample B-2 (ZrNSi20) is prepared. The coating thickness of sample B-2 is measured to be 720nm.
[0044] Comparative Example 3
[0045] Referring to Table 1, the difference between Comparative Example 3 and Example 1 is that the silicon target power of the Zr-N-Si surface layer of Comparative Example 3 is a DC power supply of 50W, and the other parameters are the same as those of Example 1. After sputtering, the surface of the prepared stainless steel specimen changes from silvery white to dark gray, and sample B-3 (ZrNSi50) is prepared. The coating thickness of sample B-3 is measured to be 850nm.
[0046] It is particularly noted that all the embodiments and comparative examples have a Zr bonding layer of the same thickness.
[0047] Table 1: Zr bonding layer, comparative examples 1-3, and coating parameters of examples 1-3
[0048]
[0049] Coating detection and analysis methods and equipment
[0050] The coating thickness was obtained by measuring the step depth using a surface profilometer (DektakXT, Bruker, Germany).
[0051] The cross section of the coating was obtained by cutting the surface of an unpolished silicon wafer with a diamond knife and then breaking it apart along the track using external force. For the cross section of the Zr / ZrNSi-Grad gradient multilayer film, the cross section was further polished using an argon ion polisher (IM5000, Hitachi, Japan). Then, the cross section of the coating was observed using a field emission scanning electron microscope (FESEM, JEOL JBM-7800F, Japan) and (FESEM, SEM5000, CIQTEK, China).
[0052] The crystal structure of the coating was detected using a grazing incidence X-ray diffractometer (GIXRD, BRUKER D8 Advance, Germany). In order to study the effect of silicon content on the structural evolution, a transmission cross-section sample of the Zr / ZrNSi-Grad coating on the AISI304 substrate was prepared using a focused ion beam electron microscope (FIB, Helios 5CX, Thermo Fisher Scientific, USA), and then the cross-section was detected and analyzed using a high-resolution transmission electron microscope (HRTEM, Talos F200S, Thermo Scientific, USA).
[0053] The chemical composition of the coating was detected by X-ray photoelectron spectroscopy (XPS, ESCSLAB 250Xi, Thermo Scientific, USA).
[0054] The hardness and elastic modulus of the coatings were measured by a nanoindentation system (G200, KLA Corporation, USA) equipped with a Berkovich diamond indenter for continuous stiffness measurement.
[0055] The wear resistance of the deposited coatings on AISI 304 stainless steel was evaluated by reciprocating dry friction tests using a tribometer (TRB, Anton Paar, Austria).
[0056] Coating test results
[0057] Figure 1 It is a schematic diagram of the structure of the above comparative examples 1-3 and embodiment 1 of the present invention, wherein, Figure 1 (a) is a schematic diagram of the coating structure of Comparative Example 1 or Comparative Example 2 or Comparative Example 3, ZrN is Comparative Example 1, ZrNSi20 is Comparative Example 2, and ZrNSi50 is Comparative Example 3. Figure 1 (b) is a schematic diagram of the coating structure of Example 1.
[0058] Optical photos and SEM cross sections of the coating are shown in Figure 2 In the figure, the upper row (a)-(d) are optical photographs of Comparative Examples 1-3 and Example 1, respectively, and the lower row (e)-(h) are SEM cross-sectional views corresponding to the upper row (a)-(d), namely (e) is the SEM cross-sectional view of (a), (f) is the SEM cross-sectional view of (b), (g) is the SEM cross-sectional view of (c), and (h) is the SEM cross-sectional view of (d). Figure 2It can be observed from (a) to (d) that the ZrN film sample is golden yellow. When Si is added to the ZrN film system, the color of the film changes from golden yellow to dark gray. This is because when Si is added, Si3N4 amorphous is formed, and the ZrN grain size is reduced. When visible light is irradiated to the film, multiple refractions, scattering, and absorption occur, resulting in a reduction in reflected light.
[0059] A 54 nm thick Zr bonding layer can be clearly observed. Figure 2 (e)-(g) were taken in secondary electron imaging mode, while Figure 2 (h) was taken in backscattered electron imaging mode, so the color of the Zr layer appears different. For the pure ZrN coating, no columnar structure was observed, indicating that the coating may not grow along certain columnar crystals due to the applied substrate bias. For the Si-doped ZrN coating (see Figure 2 In (f) and (g), the cross section is much smoother than that of the ZrN coating. Figure 2 In (h), the Zr bonding layer and the ZrN surface layer can be clearly observed. Since the silicon target power of each sublayer is slightly different during deposition, the chemical composition difference is also small. Therefore, the interface between the Zr-N-Si sublayers is not clear enough. However, each sublayer can still be roughly resolved in the cross section, indicating the formation of a gradient multilayer structure.
[0060] Figure 3 It is the element content diagram of comparative examples 1-3, which shows the atomic concentrations of Zr, N and Si elements in the coating. By calculating the nuclear level peak areas of Zr3d, N1s and Si2p respectively, it can be found that the Zr content in the ZrN coating of comparative example 1 is 54.7% and the N content is 45.3at.%. The Zr / N ratio is about 1.21:1, which is close to the stoichiometric value of ZrN. When the Si target power is set to 20W, that is, the ZrNSi20 coating of comparative example 2, the atomic concentration of Zr decreases from 54.7at.% to 44.5at.%, the atomic concentration of Si becomes 12.0at.%, and the atomic concentration of N decreases from 45.3at.% to 43.5at.%. When the Si target power reaches 50W, that is, the ZrNSi50 coating of comparative example 3, the atomic concentration of Zr decreases to 34.9at.%, the atomic concentration of Si is 18.0at.%, and the atomic concentration of N increases to 47.1at.%. In conclusion, the incorporation of silicon into ZrN coatings leads to an increase in the silicon content, but the Zr content shows a decreasing trend, while the N content remains in the range of 43.5 at.% to 47.1 at.%.
[0061] Figure 4 is the GIXRD diagram of Comparative Examples 1-3 and Example 1, Figure 4The GIXRD patterns of the coatings of Zr, Zr / ZrN (Comparative Example 1), Zr / ZrNSi20 (Comparative Example 2), Zr / ZrNSi50 (Comparative Example 3) and Zr / ZrNSi-Grad (Example 1) are shown in FIG. 1 . For the Zr coating, in addition to the main peak of (110), characteristic peaks of (001), (002), (300) and (112) are also detected according to JCPDS#26-1399, which indicates that the deposited Zr layer is a typical hexagonal crystal structure. In the Zr / ZrN coating, there are no characteristic peaks of the Zr layer. According to JCPDS#31-1493, characteristic peaks of ZrN, such as (111), (200), (220), (311) and (222), are detected. Based on the main peak of ZrN (200), the average crystal size is calculated to be 16.6 nm. In the Zr / ZrNSi20 coating, the ZrN (111) peak becomes a bun peak. Only one ZrN (200) characteristic peak is detected. The crystal size is calculated to be 8.5nm. For the Zr / ZrNSi50 coating, there is only one bun peak on the characteristic peak of ZrN (111), indicating that the ZrNSi50 coating is completely amorphous. This shows that excessive incorporation of Si will destroy the original crystal structure of the ZrN coating and lead to ZrN amorphization. The Zr / ZrNSi-Grad coating has all the characteristic peaks of the ZrN coating, such as (111), (200), (220), (311) and (222).
[0062] Figure 5 is the cross-sectional HRTEM image and selected area electron diffraction pattern of Example 1, and the cross-sectional transmission image of the Zr / ZrNSi-Grad multilayer film ( Figure 5 As can be seen in (b), the multilayer film has a clear interface. The ZrN surface layer presents a contrasting dark gray, indicating that it has a highly crystalline structure. However, among the silicon-doped ZrN sublayers, only the ZrNSi20 layer has a small number of dark spots in the gray matrix, indicating that its crystallinity is poor. When the silicon target power is increased to 30W, the ZrNSi30 sublayer has completely become amorphous. Figure 5 (b) shows the selected area electron diffraction pattern produced by the multilayer coating. Referring to JCPDS#31-1493, the indices of these patterns are (111), (002), (022), (222) and (311), which is consistent with Figure 4 The GIXRD results in are completely consistent.
[0063] Figure 6 is AISI304, the loading and unloading curves and hardness curves of Comparative Examples 1-3 and Example 1, Figure 6(a) shows the load-displacement curves of the coating and AISI304 stainless steel substrate at a penetration depth of 500 nm. The results show that the maximum loads are 66 mN, 61 mN, 59 mN, 64 mN, and 20 mN, respectively, indicating that the Zr / ZrN coating (Comparative Example 1) is the hardest, followed by the Zr / ZrNSi-Grad coating (Example 1). Figure 6 The hardness-displacement curve is plotted in (b). For the AISI304 substrate, the hardness drops rapidly and then remains at 4.2 GPa. The hardness of the coating rises rapidly to a peak value and then gradually decreases. The sudden increase in hardness when the displacement depth is less than 10 nm is the result of the initial elastic contact and the indenter size effect. The study found that at the same displacement, the hardness of Zr / ZrNSi-Grad is 19.3±0.7 GPa, which is higher than that of Zr / ZrNSi20 (Comparative Example 2) and Zr / ZrNSi50 (Comparative Example 3), indicating that the gradient structure has a hardening effect. The hardness and elastic modulus are shown in Table 2. As for the coating, the ZrN coating shows the highest elastic modulus (278.5±4.0 GPa) and hardness (26.2±0.9 GPa), while the coating with the highest silicon content (i.e., 18% in ZrNSi50) shows the lowest elastic modulus (278.5±4.0 GPa) and hardness (26.2±0.9 GPa). The elastic modulus of the ZrNSi-Grad coating is 216.8±3.1GPa and the hardness is 19.3±0.7GPa, which are relatively high. Its hardness is at least 4.6 times that of the AISI304 substrate (i.e., 4.2±0.3GPa). These changes in the elastic modulus and hardness of the Zr-N-Si coating after the addition of Si may be due to the possible high volume fraction of the amorphous phase in the coating.
[0064] Table 2: Hardness, elastic modulus, friction coefficient and wear rate of AISI304, comparative examples 1-3 and embodiment 1
[0065]
[0066] Figure 7 The surface morphology and chemical composition of the wear marks after friction between Comparative Examples 1-3 and Example 1 and AISI304 steel ball are as follows: Figure 7 In (a), we find that the surface is uniformly worn and there are some protrusions in the wear track, indicating the presence of wear particles during the wear process. Elements from the AISI304 matrix, such as Fe, Ni, and Cr, are uniformly distributed in the wear track. C and O elements may come from environmental adsorption or oxidation reactions.
[0067] For Zr-N-Si coatings (see Figure 7In (b)-(e), (b) is Comparative Example 1, (c) is Comparative Example 2, (d) is Comparative Example 3, and (e) is Example 1), and the wear mechanism is similar. The presence of grooves and pitting accumulation areas in the wear track indicates the presence of wear particles during the wear process. Some of the darker coating materials are still attached to the coating surface. The other coatings on the wear track have been completely worn away. Therefore, the AISI304 substrate below is exposed to the air. Elements in the coating (Zr, Si, N), substrate (Fe, Ni, Cr), and environment (O, C) are all detected. In the residual coating area, coating elements (Zr, Si) and environmental elements (O and C) were detected, which means that the residual coating material was oxidized during the wear process. Therefore, the wear process is determined by wear and oxidation. We note that the residual coating area in the wear track increases with the amount of Si incorporated into the ZrN coating, and ZrNSi-Grad has the largest residual coating material area in the wear track. In other words, the doping and composition gradient structure of silicon can greatly improve the adhesion strength between the coating and the AISI304 substrate, thereby improving the wear resistance, which is consistent with the results of the wear rate (see Table 2).
[0068] Figure 8 is AISI304, the wear scar depth, width and wear rate of Comparative Examples 1-3 and Example 1, Figure 8 The depth, width and wear rate of the wear track are plotted against the AISI304 ball, indicating that the AISI304 substrate is well protected by the Zr-N-Si coating. The study found that the wear track of the AISI304 substrate was the deepest (8.15 μm) and the widest (1411 μm), indicating severe wear. The wear track of the ZrNSi-Grad coating (Example 1) was relatively shallow (3.31 μm) and narrowest (587 μm), which means the best wear resistance. For the Zr-N-Si single-layer coating (ZrN in Comparative Example 1, ZrNSi20 in Comparative Example 2, and ZrNSi50 in Comparative Example 3), the depth of the wear track was between 3.78 and 4.09 μm, and the width of the wear track was between 678 and 955 μm, which was at least half smaller than that of the AISI304 substrate, indicating enhanced wear resistance. Therefore, the wear rate of AISI304 was the highest, at 5.22±1.03×10 -4 mm -3 / (Nm), while the wear rate of ZrNSi-Grad coating is the smallest, which is 0.62±0.05×10 -4 mm -3 / (Nm). With the increase of Si content in Zr-N-Si coating, the wear rate increased from 1.26±0.18×10 -4 mm -3 / (Nm) decreased to 0.75±0.07×10 -4 mm -3 / (Nm).
[0069] Fig. 9 The wear track surface and cross-sectional deformation of Example 1. In order to reveal the deformation mechanism of the multilayer film and AISI304 during wear, the cross-sectional wear track of the Zr / ZrNSi-Grad coating was observed by HRTEM (see Fig. 9 ). Abrasive particles, residual coating, grooves and unworn coating can be clearly observed on the wear scar. Fig. 9 In (a), area A is Fig. 9 Magnified in (b). A carbon / tungsten double-layer protective film is deposited on the right side of the wear scar for sampling by transmission electron microscopy. Fig. 9 (c) shows a cross-sectional TEM image of the wear scar. It can be clearly observed that the coating on the right is broken into small segments, but it is still a whole and firmly attached to the AISI304 substrate. Part of the coating on the left peels off from the substrate and overlaps the coating on the right. The AISI304 substrate undergoes severe plastic deformation, forming a curved shape. The coating on top mimics the deformed AISI304 substrate, forming a curved profile. Due to the plastic deformation of the substrate, through cracks appear in the ZrN and ZrNSi20 layers (see Fig. 9 (c)). However, these cracks are blocked or deflected by the amorphous Zr-N-Si sublayer (see Fig. 9 (d) and (e)). This indicates that the Zr bonding layer and the amorphous Zr-N-Si sublayer can withstand the deformation of the AISI 304 substrate due to their large plastic deformation capacity. Therefore, the Zr / ZrNSi-Grad coating can adhere to the deformed substrate and exhibit excellent wear resistance.
[0070] The sample preparation, characterization and detection instruments used in the present invention are as follows: M230 multi-target magnetron sputtering coating system, Beijing Weikai Technology Co., Ltd.; G200 nanoindenter, KLA Corporation of the United States; TRB friction and wear tester, Anton Paar of Austria; JBM-7800F field emission scanning electron microscope, JEOL Ltd.; ESCSLAB 250Xi, Thermo Fisher Scientific of the United States; SEM5000 field emission scanning electron microscope, Guoyi Quantum Technology (Hefei) Co., Ltd.; D8ADVANCE X-ray diffractometer, Bruker of Germany; argon ion polisher, Hitachi of Japan; Helios5CX focused ion beam electron beam dual beam electron microscope, Thermo Fisher Scientific of the United States; Talos F200S high-resolution field emission transmission electron microscope.
[0071] The serial numbers of the above embodiments of the present invention are only for description and do not represent the advantages or disadvantages of the embodiments.
[0072] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation modes, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which are within the protection of the present invention.
Claims
1. An amorphous-nanocrystalline gradient multilayer coating, characterized in that: It includes a Zr layer, a ZrNSi50 layer, a ZrNSi40 layer, a ZrNSi30 layer, a ZrNSi20 layer and a ZrN layer which are deposited in sequence.
2. The amorphous-nanocrystalline gradient multilayer coating according to claim 1, characterized in that: In the coating, the thickness of the Zr layer is 52-56 nanometers, the thickness of the ZrNSi50 layer is 105-110 nanometers, the thickness of the ZrNSi40 layer is 112-117 nanometers, the thickness of the ZrNSi30 layer is 105-110 nanometers, the thickness of the ZrNSi20 layer is 110-115 nanometers, and the thickness of the ZrN layer is 92-97 nanometers.
3. A method for preparing an amorphous-nanocrystalline gradient multilayer structure coating as claimed in claim 1 or 2, characterized in that: A multi-target magnetron sputtering coating system was used to deposit a Zr layer, a ZrNSi50 layer, a ZrNSi40 layer, a ZrNSi30 layer, a ZrNSi20 layer and a ZrN layer on the substrate surface from bottom to top in sequence through a magnetron sputtering deposition process.
4. The method for preparing an amorphous-nanocrystalline gradient multilayer structure coating according to claim 3, characterized in that: In the magnetron sputtering deposition process, the argon gas introduced is 35-45 sccm, the nitrogen gas introduced is 10-20 sccm, and the deposition time is 170-190 min.
5. The method for preparing an amorphous-nanocrystalline gradient multilayer structure coating as claimed in claim 3, characterized in that: The magnetron sputtering targets used were zirconium targets with a purity of 99.95% and silicon targets with a purity of 99.99%.
6. The method for preparing an amorphous-nanocrystalline gradient multilayer structure coating according to claim 3, characterized in that: Before the coating is deposited, the substrate surface is first polished to obtain a mirror-like substrate, and the substrate and the silicon wafer substrate are ultrasonically cleaned in anhydrous ethanol for 5-15 minutes to remove surface oil stains.
7. The method for preparing an amorphous-nanocrystalline gradient multilayer structure coating according to claim 6, characterized in that: The treatment before coating deposition also includes vacuum in the sputtering chamber exceeding 5×10 -6 After 30 to 400 sccm, argon gas with a flow rate of 30 to 50 sccm is introduced to generate argon ions under the action of a 50 W radio frequency power supply, and the substrate is ion-etched for 3 to 8 minutes to remove impurities adsorbed on the substrate surface.
8. Use of an amorphous-nanocrystalline gradient multilayer structure coating as claimed in claim 1 or 2 or a method for preparing an amorphous-nanocrystalline gradient multilayer structure coating as claimed in any one of claims 3 to 7 in preparing austenitic stainless steel surface coating.